2017
DOI: 10.1016/j.biocontrol.2017.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Biological control of septoria leaf blotch and growth promotion in wheat by Paenibacillus sp. strain B2 and Curtobacterium plantarum strain EDS

Abstract: Keywords:Wheat septoria leaf blotch Paenimyxin Paenibacillus sp. strain B2 Curtobacterium plantarum Flavonoids Salicylic acid Jasmonic acid Reactive oxygen species A B S T R A C T Many of the non-pathogenic endophytic bacteria that reside in plant roots promote plant growth as well as protection against pathogens attack. However, little is known about their mode of action in wheat. We have previously demonstrated the potential of Paenibacillus sp. strain B2 (PB2) to stimulate plant defense mechanisms via its p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 44 publications
4
32
0
Order By: Relevance
“…The content of chlorophyll is related to the intensity of photosynthesis directly; when treated with LMM15, the content of chlorophyll was 25.0% higher than in the control. All of the above data reflect that LMM15 had significant effect on plants growth promoting, and this has already been described with other BCAs [ 45 ].…”
Section: Resultssupporting
confidence: 79%
“…The content of chlorophyll is related to the intensity of photosynthesis directly; when treated with LMM15, the content of chlorophyll was 25.0% higher than in the control. All of the above data reflect that LMM15 had significant effect on plants growth promoting, and this has already been described with other BCAs [ 45 ].…”
Section: Resultssupporting
confidence: 79%
“…B. sorokiniana ) at micromolar concentrations [56,58]. In addition, data presented here confirm results of other authors showed the role defensins in protection of wheat and other plants against root diseases that are inefficiently controlled by fungicides [31,32]. Thus, we can expect that gene expression of these defensive peptides in seedlings grown from PME-treated seeds might also contribute to wheat protection against root rot causative agents under field conditions.…”
Section: Discussionsupporting
confidence: 89%
“…Seed treatments with biocontrol microorganisms or their biomolecules conjointly with other management procedures (healthy seeds, resistant cultivars, rotation with appropriate non-host crops, correct selection of fertilizers) might be an approach for improving the systems of integrated wheat protection from FCR and CRR without increasing the chemical impact in cereal-growing regions [19]. To implement this approach, biocontrol microorganisms, potential biopesticides or resistance inducers, which would effectively reduce the diseases on wheat plants after application on seeds should be available [31,32]. Several years ago, we discovered that F. sambucinum FS-94 induced systemic resistance to the vascular wilt of tomato [33], and briefly reported the inhibition of some rot- or blotch-causing wheat pathogens by the metabolites of this fungus under controlled and field conditions [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Twenty percent of the carbon fixed by photosynthesis is released into the rhizosphere, which works as a nutrient-clearing house for promoting successful plant-microbe interactions [155]. In turn, plant-associated microbiota improve plant growth by enhancing the bioavailability of nutrients such as N, P, and K to plants, as well as protecting plants against phytopathogens [156]. In addition to providing a source of carbon, plant roots also supply other metabolites that are more beneficial to some microbes than others [157].…”
Section: How Root Exudates Help To Shape the Rhizobiomementioning
confidence: 99%